High diversity and widespread occurrence of mitotic spore mats in ectomycorrhizal Pezizales. Issue 6 (3rd December 2012) - Healy, R. A.; Smith, M. E.; Bonito, G. M.; Pfister, D. H.; Ge, Z. ‐W.; Guevara, G. G.; Williams, G.; Stafford, K.; Kumar, L.; Lee, T.; Hobart, C.; Trappe, J.; et al.
Abstract Fungal mitospores may function as dispersal units and/ or spermatia and thus play a role in distribution and/or mating of species that produce them. Mitospore production in ectomycorrhizal (EcM) Pezizales is rarely reported, but here we document mitospore production by a high diversity of EcM Pezizales on three continents, in both hemispheres. We sequenced the internal transcribed spacer (ITS) and partial large subunit (LSU) nuclear rDNA from 292 spore mats (visible mitospore clumps) collected in Argentina, Chile, China, Mexico and the USA between 2009 and 2012. We collated spore mat ITS sequences with 105 fruit body and 47 EcM root sequences to generate operational taxonomic units (OTUs). Phylogenetic inferences were made through analyses of both molecular data sets. A total of 48 OTUs from spore mats represented six independent EcM Pezizales lineages and included truffles and cup fungi. Three clades of seven OTUs have no known meiospore stage. Mitospores failed to germinate on sterile media, or form ectomycorrhizas on Quercus, Pinus and Populus seedlings, consistent with a hypothesized role of spermatia. The broad geographic range, high frequency and phylogenetic diversity of spore mats produced by EcM Pezizales suggests that a mitospore stage is important for many species in this group in terms of mating, reproduction and/or dispersal.